Biochemical profiles and physicochemical parameters of beef from cattle raised under contrasting feeding systems and pre-slaughter management - Pighin, Darío Gabriel; Davies, Patricio; Ceconi, Irene; Cunzolo, Sebastián Abel; Mendez, Daniel Gustavo; Buffarini, Miguel Angel; Grigioni, Gabriela Maria (CSIRO, 2022)
Diet and pre-slaughter stress are key factors that may affect the biochemical processes during conversion of muscle into meat. The aim of the present study was to evaluate the effect of two different pre-slaughter stress managements (PSM) at a slaughterhouse in Angus steers raised and finished in two contrasting feeding systems (FS grain and pasture systems), on the peri mortem muscle metabolism, and its relation to of meat quality. Results obtained showed that a higher level of pre-slaughter stress increased (P < 0.05) glucose, lactate and proteins blood levels and decreased (P < 0.05) the redness (a* parameter) of adipose tissue. Regarding feeding strategy, pasture-fed animals displayed increased (P < 0.05) levels of haematocrit and insulin concentrations, and higher (P < 0.05) muscle pH decrease during the first 3 h post mortem. Despite final pH (pH 24 h) of M. longissimus dorsi (LD) was not significantly modified, LD hardness was significantly affected by an interaction effect of FS and PSM. Lower pre-slaughter stress level led to a decrease (P < 0.05) of LD hardness in grain-fed animals. In general terms, results showed an impact of PSM and FS on meat quality through pH-independent mechanisms.